Observations of the efficacy of the artificial lens cushion plate technique in hard-core cataract surgery - Huang, ZhiQing; Zheng, MiYun; Xu, MaoDong; Cai, Lei; Song, XiaoQing (Frontiers in Medicine, 2024)
Objective: To evaluate the efficacy of intraocular lens (IOL) cushion plate technology in reducing corneal endothelial cell loss during hard-core cataract surgery compared with conventional ultrasonic emulsification.Methods: Seventy-six patients with hard-core cataracts who underwent surgery at our institution from April 2019 to June 2022 were included. The patients were divided into an observation group (IOL cushion plate technology, 38 patients) and a control group (conventional ultrasonic emulsification, 38 patients). Surgical outcomes, including the corneal endothelial cell loss rate, best corrected visual acuity (BCVA), and central corneal thickness (CCTc), were compared between the two groups.Results: Preoperative patient characteristics were similar between the groups.Postoperatively, both groups demonstrated similar BCVA and CCTc values on days 7 and 30. However, compared with the observation group, the control group presented a significantly greater rate of corneal endothelial cell loss on postoperative days 7 and 30 (P < 0.05). Intraoperative complications and postoperative complications were notably greater in the control group (P < 0.05). The observation group had reduced ultramilk time and total energy consumption (P < 0.05).endothelial cells during hard-core cataract surgery, potentially improving surgical safety and efficacy.